2019
DOI: 10.1007/s11368-019-02431-2
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and sorption structure of diphenylarsinic acid in soil clay mineral fractions using sequential extraction and EXAFS spectroscopy

Abstract: Purpose The mobility of arsenic (As) in soils is fundamentally affected by the clay mineral fraction and its composition. Diphenylarsinic acid (DPAA) is an organoarsenic contaminant derived from chemical warfare agents. Understanding how DPAA interacts with soil clay mineral fractions will enhance understanding of the mobility and transformation of DPAA in the soil-water environment. The objective of this study was to investigate the speciation and sorption structure of DPAA in the clay mineral fractions. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 62 publications
(73 reference statements)
1
9
0
Order By: Relevance
“…3(b)) in contrast to the DPAA standard, and the second shell was fitted with four C atoms at As-C 2 (the second-nearest C) distance of 2.79 Å (Table 4). The fitted As-O, As-C 1 and As-C 2 distances in the present study correspond well with the EXAFS data (Tanaka et al, 2014;Zhu et al, 2019aZhu et al, , 2019b and density functional theory (DFT) calculations (Tanaka et al, 2014) reported in the literature.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…3(b)) in contrast to the DPAA standard, and the second shell was fitted with four C atoms at As-C 2 (the second-nearest C) distance of 2.79 Å (Table 4). The fitted As-O, As-C 1 and As-C 2 distances in the present study correspond well with the EXAFS data (Tanaka et al, 2014;Zhu et al, 2019aZhu et al, , 2019b and density functional theory (DFT) calculations (Tanaka et al, 2014) reported in the literature.…”
Section: Resultssupporting
confidence: 89%
“…The two fitting approaches yielded similar results, which are listed in Table 4. The k 3 -weighted EXAFS spectra of DPAA, together with the contributions of the first and second shells, can be found in our previous study (Zhu et al, 2019a). When the RDF of the highly DPAA-contaminated soil (Fig.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations